2013
DOI: 10.1242/dev.086157
|View full text |Cite
|
Sign up to set email alerts
|

Eaf1 and Eaf2 negatively regulate canonical Wnt/β-catenin signaling

Abstract: SUMMARYEaf factors play a crucial role in tumor suppression and embryogenesis. To investigate the potential mechanism of Eaf activity, we performed loss-and gain-of-function assays in zebrafish using morpholino and mRNA injections, respectively. We found that eaf1 and eaf2 inhibit Wnt/β-catenin signaling, thereby modulating mesodermal and neural patterning in the embryo. Moreover, ectopic expression of eaf1 and eaf2 in embryos and cultured cells blocked β-catenin reporter activity. By immunoprecipitation, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
84
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(91 citation statements)
references
References 61 publications
(76 reference statements)
7
84
0
Order By: Relevance
“…In contrast, canonical Wnt signaling is diminished. As has been recently reported for other Wnt inhibitors (Flowers et al, 2012; Hayes et al, 2013; Liu et al, 2013), the reduced expression of direct Wnt targets in slc35c1 expressing embryos is consistent with an inhibitory function of Slc35C1 on Wnt signaling. Reduced intensity of nuclear β-Catenin in the “core” region (future dorsal) and the immediate Wnt target boz prior to formation of the dorsal organizer are consistent with inhibition of maternal Canonical Wnt signaling.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, canonical Wnt signaling is diminished. As has been recently reported for other Wnt inhibitors (Flowers et al, 2012; Hayes et al, 2013; Liu et al, 2013), the reduced expression of direct Wnt targets in slc35c1 expressing embryos is consistent with an inhibitory function of Slc35C1 on Wnt signaling. Reduced intensity of nuclear β-Catenin in the “core” region (future dorsal) and the immediate Wnt target boz prior to formation of the dorsal organizer are consistent with inhibition of maternal Canonical Wnt signaling.…”
Section: Discussionsupporting
confidence: 87%
“…While subsequent studies further supported its tumor suppressive activity in vivo (11,12), the molecular mechanisms underlying this tumor suppression activity remain largely unclear. Recently, though, using a zebrafish model, we found that EAF2 and EAF1, a homolog of EAF2, can negatively regulate canonical Wnt/␤-catenin signaling by binding to ␤-catenin, which may partially explain its tumor-suppressive function mechanistically (13). Interestingly, we have demonstrated that EAF2 can bind to and stabilize pVHL, a well-defined tumor suppressor involved in HIFdegradation under normoxia.…”
mentioning
confidence: 86%
“…Inactivation of EAF2 induces tumorigenesis in several organs, including lung, liver and prostate [22]. Although its mechanism of action is unknown, studies show that EAF2 functions in controlling the growth and survival of cancer cells by negatively regulating canonical Wnt/β-catenin signaling as well as the RAS-BRAF-ERK signaling pathway [23, 24]. EAF2 also reportedly binds to and stabilizes von Hippel-Lindau protein (pVHL), a tumor suppressor involved in mediating HIF1α degradation and an inhibitor of the hypoxia pathway, which suggests it is a potential metabolic regulator [25].…”
Section: Introductionmentioning
confidence: 99%